تصميم وتنفيذ آلة اختبار لدراسة تأثير خشونة السطوح على الاحتكاك والاهتراء في عقد الاحتكاك - أحمد سلامة; خضر خفيف; رانيت سويقات (Tishreen University, 2014)
قمنا خلال هذا البحث بتصميم آلة اختبار خاصة تمكننا من إجراء طيف واسع من التجارب على حالات الاحتكاك المختلفة بين السطوح المعدنية منها دراسة تأثير خشونة السطوح على الاحتكاك والاهتراء في عقد الاحتكاك وذلك حسب خشونة السطوح المنتجة. وذلك بالاستفادة من الإمكانية التي تتيحها الآلة بتغيير الشروط والبارامترات التالية ) تغيير السرعة النسبية بين السطوح المحتكة - تغيير خشونة السطوح- تغيير وسط الاحتكاك (رطب أو جاف) - تغيير الحمل) Throughout this research, we have designed a special test machine so that we can do a wide range of experiments on various cases of friction between metal surfaces in order to study the effect of surface roughness on friction and wear, depending on the roughness of the surfaces produced,  and making use of the possibility offered by the machine to change the following conditions and parameters: (changing the relative velocity between the surfaces that come into contact with each other, changing of surface roughness, the center of friction (wet or dry), and the load).